Responsible tourism: a call to action for turbulent times - Ting, Hiram; Lim, Xin Jean; Leong, Choi Meng; Cheah, Jun Hwa; Cheer, Joseph M. (Asia Business Research Corporation, 2020)
The magnitude in which global crises and the ongoing societal challenges affects our life has called for attentions to be more socially responsible, environmentally friendly and caring for the wider community. A lot has been said recently about tourism restart or recovery as a consequence of COVID-19, highlighting the need for greater pragmatism and responsibility in the midst of turbulence, further emphasising the relevance for responsible tourism practice and scholarship. The present editorial serves as a foundation that provides an overview of the development of responsible tourism, offering a synthesis of key literature and sources regarding responsible tourism that can help guide future investigations. A bibliometric analysis of responsible tourism was conducted in Web of Science (WOS) database and subsequently 94 articles were used in the final review. While the results show the relevance of sustainable practices, behavioural factors and value creation by multiple stakeholders, they underscore the need for more and better efforts to delve into and realise responsible tourism in the contemporary environment.